Bitter gourd peptides (BG) alleviate lupus progression in mice through regulation of miR-146a/BRD4 axis in macrophages - Wu, Yu; Han, Wenyan; Li, Xian; Su, Xiulan (Frontiers in Immunology, 2026)
Bitter gourd peptides (BG) possess anti-inflammatory properties. Macrophages play a pivotal role in systemic lupus erythematosus (SLE). This study aimed to evaluate the therapeutic effect of BG in lupus-prone mice and to investigate its mechanism of action via macrophage modulation. MRL/lpr mice were treated with BG, and disease indicators were assessed. In vitro, an LPS-primed, THP-1-derived macrophage model was established and treated with BG. Macrophage polarization and autophagy were analyzed by flow cytometry, Western blot, and immunofluorescence. The role of the miR-146a/BRD4 axis was examined using qPCR, dual-luciferase reporter assay, and gain/loss-of-function approaches. BG treatment alleviated lupus symptoms in mice, including renal pathology, autoantibody production, and inflammation. In tissues, BG promoted a shift in macrophage phenotype from M1- to M2-like and enhanced autophagic activity. In vitro, BG inhibited M1-like polarization, promoted an M2-like phenotype, and enhanced autophagic flux. Mechanistically, BG upregulated miR-146a, which targeted and inhibited BRD4. Both miR-146a inhibition and BRD4 overexpression reversed the cellular effects of BG on polarization and autophagy. BG mitigates lupus progression in mice, and its effects are linked to the modulation of macrophage phenotype and autophagic activity, a process associated with the miR-146a/BRD4 axis. These findings highlight a potential therapeutic avenue for SLE.